Performing Faith at Work: Dramaturgical Strategies and Religious Expression Among Employees in Aceh, Indonesia - Arfaryanda, Farabi; Fajarni, Suci; Musdawati, Musdawati (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2025)
This study explores how employees perform and negotiate their religious identities in a professional environment through the dramaturgical perspective of Erving Goffman. The research focuses on Bintang Prima Perkasa, a consumer goods distribution company in Aceh Besar, Indonesia, where Islamic values are deeply integrated into everyday organizational life. Using a qualitative descriptive–analytical approach, data were collected through in-depth interviews, participant observation, and documentation. Participants included managers, supervisors, administrative officers, sales personnel, and delivery staff selected through purposive sampling. The findings show that religiosity in the workplace operates as both a spiritual and social performance. On the front stage, employees express faith through punctual prayer, greeting with salam, and participation in collective pengajian to project professionalism and integrity. On the back stage, they practice a more personal and emotional form of worship beyond social observation. Religion serves dual functions: socially, it fosters trust, cooperation, and moral discipline; psychologically, it provides emotional stability and stress relief. Supported by organizational facilities, these practices have evolved into institutional norms that strengthen solidarity and moral order. The study concludes that religiosity in this workplace functions as a dramaturgical strategy that integrates faith, ethics, and professionalism, contributing to a cohesive and value-based organizational culture.